Factors related to Quality of Work Life in Nursing Personnel of Public Hospitals in Southern Ecuador - Urgiles-Barahona, Cristina Elisabeth; Astudillo-Romero, Xavier; Cabrera-Celi, Stefany Daniela; Quezada-Pardo, Paulina Elizabeth; Cando-Zuñiga, Joselyne Amada (Journal of Ecohumanism, 2024)
The nursing profession requires the development of competencies and skills to provide effective care to patients. To provide effective care, nurses’ quality of life (QWL) must be optimal. This study aimed to identify factors related to QWL and assess the QWL of professional nursing personnel of the southern public hospitals in Ecuador through a cross-sectional analytical study. The data were collected from a sample of 187 units of analysis, selected by simple probabilistic sampling. The ad hoc survey was applied to identify intrinsic and extrinsic factors in the work environment. Also, the APGAR test was applied for family functionality. The QWL was assessed using the CVT-GOHISALO questionnaire. Mean comparison tests were applied and selected according to the data distribution; a p-value of <0.05 was considered significant. Job integration, job satisfaction, well-being achieved through work, and management of free time showed a low global perception of QWL. QWL showed significant differences such as type of function, type of workday, perception of health status, having a diagnosed chronic disease, presence of psychological disorders, musculoskeletal disorders, having children under two years of age, and family functionality. QWL in nurses is low and modified by work, health, and family factors.